2015
DOI: 10.1097/dcr.0000000000000309
|View full text |Cite
|
Sign up to set email alerts
|

Transanal Endoscopic Microsurgery Versus Standard Transanal Excision for the Removal of Rectal Neoplasms

Abstract: Available data are limited because of a lack of randomized controlled trials. However, based on current evidence, transanal endoscopic microsurgery is oncologically superior to transanal excision for the excision of rectal neoplasms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
84
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 185 publications
(96 citation statements)
references
References 29 publications
2
84
0
2
Order By: Relevance
“…It also has the potential to further reduce the cost of TAMIS, since it is performed with a conventional laparoscopic video system, which is widely available in most institutions. Recently, a meta-analysis was performed of TEM vs. the standard TAE procedure (22). No difference was found between the techniques in the postoperative complication rate.…”
Section: Discussionmentioning
confidence: 99%
“…It also has the potential to further reduce the cost of TAMIS, since it is performed with a conventional laparoscopic video system, which is widely available in most institutions. Recently, a meta-analysis was performed of TEM vs. the standard TAE procedure (22). No difference was found between the techniques in the postoperative complication rate.…”
Section: Discussionmentioning
confidence: 99%
“…specifically, it has been demonstrated that le using any of the advanced transanal platforms (tem/transanal endoscopic operation/transanal minimally invasive surgery) results in less specimen fragmentation with a higher rate of completely intact, marginnegative excisions. 20,21,25 thus, the technique of using an advanced transanal platform seems to provide improved resection quality when compared with the Parks tae.…”
mentioning
confidence: 94%
“…Since then it has gradually gained acceptance and replaced the standard transanal excision due to its benefits of quick learning curve and better augmentation of the excised area. In a meta-analysis, Clancy et al [73] proved better oncological results when using TEM instead of standard excision. TEM is consequently an established approach, which offers a stable operating platform with magnified stereoscopic view, thus allowing precise full-thickness excision of the rectal wall as far as 15-20 cm from the anal verge.…”
Section: Advanced Clinically Approved Laparoscopic Techniquesmentioning
confidence: 99%